HALAL LABEL, CELEBRITY ENDORSERS, AND PRODUCT QUALITY: THEIR EFFECT ON MS GLOW PURCHASE DECISIONS THROUGH BRAND TRUST - Jamilah, Ismiyatul; Maksum, Maksum (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2024)
AbstractThe cosmetics industry is experiencing a rapid increase in Indonesia, including MS Glow beauty products. With the development of the cosmetics industry sector, cosmetic companies are competing to win the hearts or attention of consumers. Many factors motivate a consumer to make a purchase, including the presence of a halal label on the packaging, celebrity endorsers, and the quality of the product itself. Therefore, the purpose of this study is to test and analyze the effect of halal labels, celebrity endorsers, and product quality on purchasing decisions for MS Glow cosmetics with brand trust as an intervening variable. This research uses quantitative methods. The data used in this research is primary data, where for data collection this uses a questionnaire with a Likert scale. The study's 100 respondents were chosen through purposive sampling, and the respondents were INSTIKA students. Furthermore, SmartPLS version 3 will be used to analyze the data in this study. The results of this study indicate a significant influence between the halal label and product quality on brand trust, while celebrity endorsers have no effect on brand trust. Also, celebrity endorsers and product quality have a significant effect on purchasing decisions, while halal labels have no influence on purchasing decisions. Then, the results of the path analysis test state that the brand trust variable has a significant effect in mediating the relationship between product quality and purchasing decisions. In the meantime, factors related to brand trust do not moderate the relationship between halal labels and celebrity endorsers on purchase decisions.